2016
DOI: 10.1113/jp272907
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating Nox2 reactive oxygen species production protects dystrophic skeletal muscle from pathological calcium influx assessed in vivo by manganese‐enhanced magnetic resonance imaging

Abstract: Duchenne muscular dystrophy (DMD) is an X-linked progressive degenerative disease resulting from a mutation in the gene that encodes dystrophin, leading to decreased muscle mechanical stability and force production. Increased Nox2 reactive oxygen species (ROS) production and sarcolemmal Ca influx are early indicators of disease pathology, and eliminating Nox2 ROS production reduces aberrant Ca influx in young mdx mice, a model of DMD. Various imaging modalities have been used to study dystrophic muscle in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 61 publications
2
22
2
Order By: Relevance
“…The antioxidant NAC protects mdx muscle from ECCinduced force loss in a muscle length change-dependent manner ECC-induced force loss of isolated mdx EDL muscle is associated with oxidative stress [9,36]. We have previously shown that addition of NAC partially protects mdx EDL muscle from losing force from ECCs of a 10% length change [9], and here we confirmed this result (Fig.…”
Section: Sarcolemmal Damage Is Associated With the Muscle Length Chansupporting
confidence: 88%
“…The antioxidant NAC protects mdx muscle from ECCinduced force loss in a muscle length change-dependent manner ECC-induced force loss of isolated mdx EDL muscle is associated with oxidative stress [9,36]. We have previously shown that addition of NAC partially protects mdx EDL muscle from losing force from ECCs of a 10% length change [9], and here we confirmed this result (Fig.…”
Section: Sarcolemmal Damage Is Associated With the Muscle Length Chansupporting
confidence: 88%
“…While the ROS-based perturbations tested here by us and reported by others previously 27 , 47 , 55 , 60 all demonstrated significant protection of mdx muscle from ECC force loss, the measured protection is incomplete. Other studies have implicated elevated cytosolic calcium 61 64 , loss of neuromuscular junction or sarcolemmal membrane excitability 19 , 20 , neuronal nitric oxide synthase 25 , and Akt/PKB signaling 24 in mdx ECC force loss and our results are neither incompatible with nor mutually exclusive of such mechanisms.…”
Section: Discussioncontrasting
confidence: 54%
“…Furthermore, the exogenous administration of 7,8-dihydroneopterin showed protection comparable to other antioxidants, such as N-acetylcysteine (Whitehead et al, 2008). Other investigations have attenuated eccentric contraction-induced force loss with genetic manipulation of NADPH subunits (Loehr et al, 2016) or by supplementation with green tea extract (Buetler et al, 2002), whereas here we show that 7,8-dihydroneopterin can protect skeletal muscle from force loss in the presence of common pro-oxidants, which are abundant in dystrophic muscle (Disatnik et al, 1998).…”
Section: Eccentric Contractions Facilitate 78-dihydroneopterin Absorsupporting
confidence: 63%
“…Furthermore, the exogenous administration of 7,8‐dihydroneopterin showed protection comparable to other antioxidants, such as N ‐acetylcysteine (Whitehead et al., ). Other investigations have attenuated eccentric contraction‐induced force loss with genetic manipulation of NADPH subunits (Loehr et al., ) or by supplementation with green tea extract (Buetler et al., ), whereas here we show that 7,8‐dihydroneopterin can protect skeletal muscle from force loss in the presence of common pro‐oxidants, which are abundant in dystrophic muscle (Disatnik et al., ). Thus, elevated 7,8‐dihydroneopterin in DMD patients may describe macrophage activation, but it may also provide a muscle‐specific protective mechanism against eccentric‐induced muscle force loss and, consequently, loss of muscle function.…”
Section: Discussioncontrasting
confidence: 52%